Acoustic Emission and Apparent Charge Measurement Applied to Power Transformer Failures Identification - Teopald, Ana Beatriz Sacco [UNESP]; de Castro, Bruno Albuquerque [UNESP]; Andreoli, André Luiz [UNESP]; Ardila-Rey, Jorge Alfredo; Bittencourt, Izadora Rodrigues [UNESP]; Smith, Colin (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The presence of full-discharges in power transformers, which can be characterized by dielectric degradation between turns, is usually found in the stages preceding the total failure of the machine. Although several non-destructive techniques for monitoring these faults are applied, the Acoustic Emission technique stands out due to its low cost and ease of application. This paper uses a piezoelectric transducer to validate acoustic emission as a means to perform full-discharge evolution characterization, attaching it to a power transformer wall and applying different levels of full discharges on it. In order to validate the failure evolution, the apparent charge emitted by the flaw was calculated using a High Frequency Current Transformer (HFCT). The results presented in this article attest that acoustic emission has great potential to evaluate evolution of full-discharges in power transformers since it was found that the energy levels of the acoustic emission increase with the apparent charge.
Keywords: full discharges; Piezoelectric transducers; signal processing; transformer monitoring